Pengaruh Pengetahuan Keuangan, Sikap Keuangan, Dan Kepribadian Terhadap Perilaku Manajemen Keuangan Pada Pelaku UMKM Ekonomi Kreatif Sub Sektor Kuliner Kabupaten Malang (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to determine the effect of financial knowledge, financial attitudes, and personality on financial management behavior on MSMEs actor creative economy culinary sub-sector in Malang Regency. This research is a type of replication research. This research subjects were 41 MSME ctreative economy culinary sub-sector in Malang Regency. Data colleection method is done by using a questionnaire. The analytical method used is the validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, and hypothesis testing. The result showed that financial knowledge influences financial management behavior, financial attitude does not affect financial management behavior, and personality does not affect financial management behavior. Keywords: : financial knowledge, financial attitude, personality, financial management behavior